Correlates of ChatGPT use intention among freshmen health sciences students - Penuela, Ayesha; Habaña, Maylin P.; Oducado, Ryan Michael F.; Pedroso, John Erwin; Bonzo, Ernie; Tamdang, Khen (Journal of Education and Learning (EduLearn), 2025)
The proliferation of ChatGPT in educational contexts and incorporating such technology into students’ academic lives raise intriguing questions. Understanding the factors influencing the intention to adopt this novel technology is necessary for better integration and utilization. This study determined the correlates of intention to use ChatGPT among undergraduate health sciences students. Data for this correlational study was gathered through an online survey and was answered by 153 students of health sciences programs at a private school in the Philippines. Spearman’s correlational analysis demonstrated that perceived credibility, perceived usefulness, perceived social influence, attitude, perceived usefulness, and perceived ease of use significantly correlated with intention to use ChatGPT among health sciences students. These findings are crucial for educational practitioners looking for ways to enhance students’ learning outcomes and experiences. By leveraging technology like ChatGPT, they can potentially enrich educational experiences and better prepare students for the advanced technological landscape of healthcare, ultimately improving the quality of health sciences education.